APPLICATION OF PHOSPHODIESTERASE TYPE 5 INHIBITORS SILDENAFIL IN PATIENTS WITH PULMONARY HYPERTENSION - T. V. Martynyuk; Z. H. Dadacheva; V. M. Paramonov; O. A. Arkhipova; S. N. Nakonechnikov; I. Ye. Chazova (Евразийский Кардиологический Журнал)
The key component of the pathogenesis of pulmonary hypertension (PH) is endothelial dysfunction with imbalance between vasodilators and vasoconstrictors and activation of the blood coagulation system. Randomized trials showed a beneficial effect of phosphodiesterase type 5 (PDE-5) inhibitors on vascular remodelling and vasodilatation in pulmonary arterial hypertension (PAH). Sildenafil is the only PDE-5 inhibitor that is officially approved by Pharmacological Commitee in our country. PDE-5 inhibitors by blocking the breakdown of cyclic guanosinemonophosphate (cGMP) resulted in prolongation of the action of vasoactive mediators including nitric oxide (NO) that cause vasodilation and antiproliferation in the lung. Sildenafil demonstrated the efficacy in uncontrolled clinical studies in pts with idiopathic pulmonary hypertension, PAH due to systemic connective tissue disease, congenital heart defects, with pulmonary embolism. 25-75mg at doses 2-3 times a day in patients with improved pulmonary hemodynamics, exercise tolerance. Basis for the authorization of this drug in the setting of PAH was a large randomized, placebo-controlled trial in which different doses of sildenafil were assessed in 278 patients presenting with idiopathic PAH, PAH related to connective tissue disease or congenital systemic to pulmonary shunts surgically corrected. After three months of treatment significant hemodynamic and functional class improvements were noted in every sildenafil group as compared to placebo. An approved dose is 20 mg three times a day, but in clinical practice often higher doses of 40-80 mg to 3 times per day are in need. Stable long-term efficacy of Sildenafil was observed with the dose of 80 mg 3 times a day in SUPER-2 trial. PACES trial demonstrated the efficacy of sildenafil in combination with intravenous epoprostenol.